2015
DOI: 10.1177/1078087415589193
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Across the Divides of Race/Ethnicity

Abstract: There exists an active discussion as to the effects of racial/ethnic composition on community connection. Research has suggested that racial segregation is beneficial to one's community connection. To explore this dynamic, we investigate how an individual's community connection is determined by the racial/ethnic segregation of his or her neighborhood, among other independent variables. We implement multilevel models using individual data from the socioeconomic status of a neighborhood explains much of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…First, we include a measure of social cohesion, a composite score used in several studies 49,50 based on the principal component analysis (PCA) of respondents' answers to the following three questions: (1) Willingness, BWould you say that most people in your neighborhood are always, often, sometimes, rarely, or never willing to help their neighbors?^From always to never, we coded from 5 to 1. (2) Belonging, BDo you strongly agree, agree, disagree, or strongly disagree that you feel that you belong and are part of your neighborhood?^We coded the answers with a four-level Likerttype scale where 4 means strongly agree, and 1 indicates strongly disagree.…”
Section: Methodsmentioning
confidence: 99%
“…First, we include a measure of social cohesion, a composite score used in several studies 49,50 based on the principal component analysis (PCA) of respondents' answers to the following three questions: (1) Willingness, BWould you say that most people in your neighborhood are always, often, sometimes, rarely, or never willing to help their neighbors?^From always to never, we coded from 5 to 1. (2) Belonging, BDo you strongly agree, agree, disagree, or strongly disagree that you feel that you belong and are part of your neighborhood?^We coded the answers with a four-level Likerttype scale where 4 means strongly agree, and 1 indicates strongly disagree.…”
Section: Methodsmentioning
confidence: 99%
“…Ethnoracial minority residents living in homogenous nonwhite neighborhoods within segregated regions have been found to enjoy a greater sense of trust compared to ethnoracial minorities who live elsewhere. This trust relates to a strong sense of community (McMillan ), often measured by forces of social cohesion like social capital or community connection (Bakker and Dekker ; Gibbons and Yang ; Neal and Neal ; Usher ; Uslaner ).…”
Section: Literaturementioning
confidence: 99%
“…Beyond the demographic questions, variables of individual social cohesion include a measure of community connection , a means‐centered composite score comprised of several factors associated with one's sense of community including trust of neighbors, sense of belongingness to a neighborhood, and the likelihood one will collaborate with neighbors (Dean et al. ; Gibbons and Yang ; Greif ; McMillan ; Sampson ). Following on past research (Gibbons and Yang ), this score is determined by PCA reported in the Supplamental Tables.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations